The regulatory factor PcRFX1 controls the expression of the three genes of β-lactam biosynthesis in Penicillium chrysogenum - Domínguez-Santos, Rebeca; Martín, Juan-Francisco; Kosalková, Katarina; Prieto, Carlos; Ullán, Ricardo V.; García-Estrada, Carlos (Fungal genetics and biology, 2012)
► A novel transcription factor, PcRFX1, has been characterized in Penicillium chrysogenum. ► PcRFX1 controls the expression of the three penicillin biosynthetic genes. ► Morphology and development seemed not to be controlled by this transcription factor. ► A global analysis of processes putatively regulated by PcRFX1 was carried out. Penicillin biosynthesis is subjected to a complex regulatory network of signalling molecules that may serve as model for other secondary metabolites. The information provided by the new “omics” era about Penicillium chrysogenum and the advances in the knowledge of molecular mechanisms responsible for improved productivity, make this fungus an excellent model to decipher the mechanisms controlling the penicillin biosynthetic pathway. In this work, we have characterized a novel transcription factor PcRFX1, which is an ortholog of the Acremonium chrysogenum CPCR1 and Penicillium marneffei RfxA regulatory proteins. PcRFX1 DNA binding sequences were found in the promoter region of the pcbAB, pcbC and penDE genes. We show in this article that these motifs control the expression of the β-galactosidase lacZ reporter gene, indicating that they may direct the PcRFX1-mediated regulation of the penicillin biosynthetic genes. By means of Pcrfx1 gene knock-down and overexpression techniques we confirmed that PcRFX1 controls penicillin biosynthesis through the regulation of the pcbAB, pcbC and penDE transcription. Morphology and development seemed not to be controlled by this transcription factor under the conditions studied and only sporulation was slightly reduced after the silencing of the Pcrfx1 gene. A genome-wide analysis of processes putatively regulated by this transcription factor was carried out in P. chrysogenum. Results suggested that PcRFX1, in addition to regulate penicillin biosynthesis, is also involved in the control of several pathways of primary metabolism.